ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI BERWIRAUSAHA DI KOTA PEKANBARU - Nasri Bachtiar; Reni Amalia (Jurnal Kependudukan Indonesia, 2012)
Today, in Pekanbaru the situation of an abundant manpower supply but limited market capacity makes people, unable to find work, anxious to create their own businesses (self employment). Using primary data, the goal of this paper is to show the individual level determinants of self employment. A logistic regression model is used to estimate different aspects of choices between self employment and working for a salary. This study argues that age, gender, education, Chinese ethnicity and marital status play a significant role in the decision to become self employed in the city of Pekanbaru. As well, other variables such as Melayu or Minang ethnicity and migrant status play a small role in determining who is self employed. Most of the coefficients are positive, except for education and Melayu ethnicity with the Minang and Chinese ethnicity probability to become self employed better than that of the Melayu. There are some suggestions that Minang and Chinese people may place a higher value on entrepreneurship than do the Melayu. Indeed, the Chinese having faced severe discrimination have been pushed into self employment in large numbers. This research, however, also shows that the differences in decisions to be self employed vary substantially across ethnic lines. Therefore, the development of entrepreneurship requires a systematic and integrative approach to find out just what is involved in creating an environment conducive to the growth and development of entrepreneurship.Key Words : Self Employment, Personal Characteristics, Ethnic, Pekanbaru City